NONLINEAR DYNAMICS ANALYSIS OF A SINGLE-DISK FLEXIBLE RUBBING ROTOR - LIU DeQiang (Jixie qiangdu)
A rotor system in rubbing is shown to exhibit complex phenomena including period-doubling bifurcation,quasiperiodic and chaotic motions due to itsstrongly nonlinear dynamic characteristics. Based on the mechanical model of a single-disk flexible Jeffcott rotor,the fourth-order Runge-Kutta method with variable step size was used for numerical simulation. The essential relationship between the model parameters and the dynamic characteristics of the system is studied by used periodic bifurcation diagrams,axis trajectory diagrams,Poincaré section diagrams and maximum rubbing force diagrams. The simulation results show that the change of stiffness ratio has great influence on the dynamic characteristics of the system. With the increase of damping coefficient,the type of periodic motion mode of the system decreases obviously,and the chaotic region decreases accordingly. When the eccentricity ratio increases,the dynamic characteristics of the system become more complex. Meanwhile,the maximum rubbing force increases significantly,and the rubbing events of the rotor system become more serious. The calculation and analysis in this paper may be helpful for avoided rubbing events and limited maximum friction in the design of single-disk flexible rotor.